2017
DOI: 10.1016/j.bbr.2017.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Implicit self-other discrimination affects the interplay between multisensory affordances of mental representations of faces

Abstract: Face recognition is an apparently straightforward but, in fact, complex ability, encompassing the activation of at least visual and somatosensory representations. Understanding how identity shapes the interplay between these face-related affordances could clarify the mechanisms of self-other discrimination. To this aim, we exploited the so-called "face inversion effect" (FIE), a specific bias in the mental rotation of face images (of other people): with respect to inanimate objects, face images require longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Accuracy for letters in their normal upright form decreased up to 180°, with a slight increase for stimuli rotated at 270°. Similar results have previously been found in mental rotation tasks with stimuli of different kinds (see e.g., Kosslyn et al, 1998; Hyun and Luck, 2007; Milivojevic et al, 2011; Zeugin et al, 2017), further corroborating that our experimental manipulation was effective and that mental rotation of our haptic letter stimuli indeed took place. The significant interaction between factors Condition and Angle illustrates the fact that mental rotation of familiar stimuli was more successful than for unfamiliar stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Accuracy for letters in their normal upright form decreased up to 180°, with a slight increase for stimuli rotated at 270°. Similar results have previously been found in mental rotation tasks with stimuli of different kinds (see e.g., Kosslyn et al, 1998; Hyun and Luck, 2007; Milivojevic et al, 2011; Zeugin et al, 2017), further corroborating that our experimental manipulation was effective and that mental rotation of our haptic letter stimuli indeed took place. The significant interaction between factors Condition and Angle illustrates the fact that mental rotation of familiar stimuli was more successful than for unfamiliar stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…The participants in our second experiment showed poor performance (lower recognition rates and longer recognition time) for the non-prototypical shapes than the prototypical ones due to the mental rotation effect (Shepard and Metzler, 1971). Similar results were also reported in the literature for the mental rotation experiments conducted with different types of stimuli (Milivojevic et al, 2011;Theurel et al, 2012;Zeugin et al, 2017;Tivadar et al, 2019). Theurel et al (2012) also observed a prototype effect in their experiments conducted with congenitally blind and blindfolded adolescents on the haptic recognition of geometrical shapes.…”
Section: Geometric Complexity Of Shape Affects the Tactile Perceptionsupporting
confidence: 87%
“…Further, structural data supported these abnormalities in both EF and reading networks. Hinting at the importance of multisensory processing ( Zeugin et al, 2017 ), decreased FA has been found in bilateral fronto-temporal and left temporo-parietal white matter regions ( Steinbrink et al, 2008 ) and left middle and inferior temporal gyri and left arcuate fasciculus ( Silani et al, 2005 ; Vandermosten et al, 2012 ). Decreased FA was found in bilateral temporo-parietal white matter regions in another sample of adults ( Klingberg et al, 2000 ), and a decrease in FA in all four lobes has been seen ( Richards et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, structural data supported these abnormalities in both EF and reading networks. Hinting at the importance of multisensory processing (Zeugin et al, 2017), decreased FA has been found in bilateral fronto-temporal and left FIGURE 3 | Neural circuit dysfunction related to reading circuits in teenagers (ages 13-21) with dyslexia. Decreased activation in the left inferior frontal gyrus (Wimmer et al, 2010;Steinbrink et al, 2012), left parietal lobule (Hoeft et al, 2007;Wimmer et al, 2010;Steinbrink et al, 2012), left fusiform gyrus (Hoeft et al, 2007;Desroches et al, 2010), and left temporal gyrus (Wimmer et al, 2010;Steinbrink et al, 2012) and increased activation in the left inferior frontal gyrus (Hoeft et al, 2007), left middle frontal gyrus (Hoeft et al, 2007), left caudate (Hoeft et al, 2007), and left thalamus (Hoeft et al, 2007) related to EF in children ages 13-21 at risk for dyslexia.…”
Section: Neural Circuits Related To Ef In Adults With Dyslexia (22 Years and Older)mentioning
confidence: 99%